The Utilizing Suno.Ai Technology to Enhance Arabic Listening Skills in Foreign Language Education - Sa'diyah, Khusnul Khotimah Halimatus; Muassomah, Muassomah; Qomari, Nur; Sulaiman, Sulaiman Hasan (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
This study explores using Suno.Ai, an AI-powered platform, to teach maharah istima' (listening comprehension) at Thursina International Islamic Boarding School (IIBS). While previous research on digital media has focused mainly on English instruction, few studies have explored the use of AI in Arabic listening education, particularly within Islamic boarding schools. This research addresses that gap by analyzing how Suno.Ai supports Arabic vocabulary acquisition and student engagement. This study employs a qualitative case study design; data were collected through classroom observations and teacher-student interviews and then analyzed thematically and interpretively. Findings show that Suno.Ai enhances students' motivation and comprehension with adequate facilities and teacher guidance, although challenges like internet instability and low digital literacy persist. The novelty of this study lies in its contextual application of AI tools in Arabic language pedagogy. It contributes theoretically by expanding discourse on AI in language learning and offering insights into AI's effective integration in Arabic listening instruction.